TRANSFORMING RURAL EDUCATION WITH DIGITAL ASSESSMENT TOOLS: A CASE STUDY OF SOCRATIVE IN SAROLANGUN, INDONESIA - Saleh Yaakub; Wawan Joko Pranoto; Ika Safitri Windiarti; Rida Priyanti (LPPM Universitas Muhammadiyah Jambi, 2025)
Purpose: This study explores the implementation of Socrative, a digital assessment tool, to enhance teaching and learning in rural primary schools in Sarolangun, Indonesia. It addresses persistent challenges such as limited digital literacy, inadequate infrastructure, and low student engagement. The study aligns with the Indonesian government’s